Effectiveness of root-bark extract from Salvadora persica against the growth of certain molecularly identified pathogenic bacteria. (April 2018) - Salem, Mohamed Z.M.; Behiry, Said I.; Salem, Abdelfattah Z.M.
Abstract: The acetone extract from root-bark of Salvadora persica L. (Salvadoraceae), is assayed for its antibacterial activity against some bacterial pathogens. By GC/MS analysis, the main chemical components of the acetone extract were found to be benzylisothiocyanate (39.4%), and benzyl nitrile (benzeneacetonitrile) (37.9%). According the extract concentrations used, the measured inhibition zones observed were between from 13.6 to 18.6 mm, 15.3–23 mm, 13.3–18.3 mm, 13.3–18.3 mm, and 12.3–19 mm, against the isolated plant bacterial pathogens namely Agrobacterium tumefaciens, Pectobacterium atrosepticum, Enterobacter cloacae, Dickeya solani and Ralstonia solanacearum, respectively, whilst it was between 8 and 12 mm, 8–9.6 mm, 8–11.6 mm, and 8–10.3 mm against Bacillus subtilis, Sarcina lutea, Escherichia coli and Staphylococcus aureus, respectively. The minimum inhibitory concentration values of the extract were between 16 and 32 μg/mL against the growth of plant bacterial, and from 1000 to 2000 μg/mL against the growth of the human bacteria. In conclusion, the acetone extract of root-bark of S. persica showed strong antibacterial activity against the plant pathogens and some activity against the human pathogens were reported. The results suggested that using the acetone extract from root-bark of S. persica as bioactive agent against the growth of the studied plant bacterial pathogens. Graphical abstract: Image 1 Highlights: Antibacterial activity of root-bark extract from Salvadora persica was assayed. Phytopathogenic bacteria isolated from front of rot/galls or newly diseased tissue. Benzylisothiocyanate, and benzyl nitrile were the most abundant compounds. The extract showed strong antibacterial activity against the plant pathogens. Weak activity against human pathogens but higher than the antibiotic used.